2016
DOI: 10.1007/s10940-016-9303-z
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Correlates of Sex Offender Residence Restriction Violation Rates

Abstract: Objectives: This research examines the contribution of social ecological factors to the variation in sex offender residence restriction (SORR) violation rates, operationalized as a sex offender residing within a buffer zone around a school or a day care.Methods: Drawing on data from two Midwestern states, we utilize a quasi-experimental cohortcontrol group design to examine the correlates of county-level SORR violation rates among a cohort of post-SORR sex offender parolees, and three counterfactual cohorts (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…3. For additional information on the propensity score matching procedure, please see Huebner et al (2014) and the electronic supplementary material to Rydberg et al (2017). 4.…”
Section: Authors' Notementioning
confidence: 99%
“…3. For additional information on the propensity score matching procedure, please see Huebner et al (2014) and the electronic supplementary material to Rydberg et al (2017). 4.…”
Section: Authors' Notementioning
confidence: 99%
“…Residence restrictions blur the line between criminal and civil legal spheres, constituting another expansion of the shadow carceral state (Beckett & Murakawa, 2012). In some states, like Missouri, residence restrictions prohibit individuals with a sexual offense from living and congregating near schools, parks, and other places where children gather (Huebner et al., 2014; Rydberg et al., 2017; Socia, 2011). Research has suggested that residence restrictions often force people to live farther away from work and social services and often preclude residence with supportive family members (Huebner et al., 2021; Levenson & Hern, 2007) as most of the available housing in major metropolitan communities is within a restricted zone (Hughes & Burchfield, 2008).…”
Section: Monetary Sanctions As Controlmentioning
confidence: 99%